Nietzsche and transhumanism : precursor or enemy? - Tuncel, Yunus (Newcastle upon Tyne, England : Cambridge Scholars Publishing, 2017)
This essay collection deals with the question of whether Nietzsche can be seen as a precursor of transhumanism or not. Debates on the topic have existed for some years, particularly in the Journal of Evolution and Technology and The Agonist. This book combines existing papers, from these journals, with new material, to highlight some of the important issues surrounding this argument. The collection addresses a variety of issues to show whether or not there is a close connection between transhumanist concerns for progress and technology and Nietzsche's ideas.
Introduction; Part I; Chapter One; Chapter Two; Chapter Three; Chapter Four; Chapter Five; Part II; Chapter Six; Chapter Seven; Chapter Eight; Chapter Nine; Part III; Chapter Ten; Chapter Eleven; Chapter Twelve; Chapter Thirteen; Chapter Fourteen; Chapter Fifteen; Contributors; Bibliography
Includes bibliographical references.
Description based on online resource; title from PDF title page (ebrary, viewed June 5, 2017).
OCLC control number change
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900 -- Criticism and interpretation; Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Superman (Philosophical concept); Philosophy; Science: general issues; Society & social sciences; PHILOSOPHY -- History & Surveys -- Modern; Superman (Philosophical concept); Electronic books; Criticism, interpretation, etc